Hubungan Antara Asupan Protein Dan Karbohidrat Dengan Status Gizi Pada Remaja Putri Di Pondok Pesantren Ta'mirul Islam Surakarta - Robbi Rodhiyya, Zidne; , Nur Lathifah Mardiyati, S.Gz., M.S; , Fitriana Mustikaningrum, SGz., M.Sc (2016)
Background : Adolescence is a period of human development. Nutritional problems that often occur in adolescents is the lack of nutritient intake and cause malnutrition status which cause nutrient intake and excess nutrients. Protein has an important rule in muscle growth and strength. Everyday, teens need 45-60 grams of protein derived from food such as meat, chicken, eggs, milk, other product, beans, tofu and soybean. Carbohyraters are the main source of energy for the body. Teen carbohydrate needs in female need 292 grams per day. Objective : To determine relationship between protein and carbohydrate intakes with nutritional status in female students at Ta'mirul Islam Boarding School of Surakarta. Research methods : This research was an observational with cross-sectional. The subject were 54 female students of class X and XII Ta'mirul Surakarta Islamic Boarding School. The sampling technique used convenience sampling method. The collection technique identity of respondents data by filling the questionnaires. Intakes of protein and carbohydrate data used Semi Quantitative Food Frequency Quenstionnairs and nutritional status used anthropometric measurements. Data analysis used to test data normality using the Kolmogorov- Smirnov test. Relationship used test the Spearman rank tests. Results : Students who had good intake was 46.3% protein, carbohydrate intake has 63.0% and 74.1% of student had normal nutritional status. The results of correlation test protein intake and nutritional status of female students obtained value of p = 0.922 and correlation between carbohydrate intake and nutritional status of female students obtained p = 0.966. Conclusion : There was no relationship between protein and carbohydrates intakes with nutritional status in females students at Ta'mirul Islamic Boarding School of Surakarta